2015
DOI: 10.4103/1119-3077.151042
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Injury: A ten-year multicenter analysis of evolution of care and risk factors for poor outcome in southeast Nigeria

Abstract: The cervical spine is the most commonly injured spinal segment in southeast Nigeria. Although treatment evolution has resulted in reduction of hospital stay, the associated mortality risk still remains high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The mean age and the male preponderance in this series are similar to other studies on CSI [4,12,20,22,23]. One of such studies found an average age of 42 years and males accounted for 76.8% of the patients [4].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The mean age and the male preponderance in this series are similar to other studies on CSI [4,12,20,22,23]. One of such studies found an average age of 42 years and males accounted for 76.8% of the patients [4].…”
Section: Discussionsupporting
confidence: 89%
“…Other causes of failed reduction were: facet lock (20.3%), worsening pain (4.1%), and over-distraction (2.7%). The reported causes of failed closed traction reduction in other studies include those already cited, as well as non-contiguous vertebral fracture at a more rostral level, facet fracture at the level of subluxation, worsening neurologic deficits, cervical disc herniation, epidural haematoma, cord oedema, arm weakness, tong pull-out, inadequate immobilisation, and poor patient status (cardiac, respiratory, and haemodynamic instability) [2,4,5,8,12,14,15,17,18,22,25]. The complications of closed traction reduction seen in our series were over-distraction (7%) (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…4 , 5 In a retrospective ten-year multicentre analysis of CSI in the southeast of Nigeria, Uche et al found a male to female distribution of 3.1:1 in the study cohort. 6 Motor vehicle accidents, fall from height, sports-related injuries and assault are the most common causes of CSI in the younger population. 7 In the elderly, non-traumatic causes of cervical spine injuries that may be due to osteoporotic compression fractures, degenerative diseases of the spine or compression fractures from spinal tumours are more prevalent.…”
mentioning
confidence: 99%